An integrated framework for lean production and marketing mix strategy toward business performance - Hamid Yaseen, Maryam (2021)
Business performance is a critical issue for organizations, especially in the food industry, which faces multiple challenges that are forcing companies in the industry to improve their strategies to remain competitive. The food industry plays a vital role in the economy of Malaysia by creating employment, market outlets, and adding value to primary agricultural products, and it accounts for about 10% of Malaysia's manufacturing output. Despite It contributed about RM21.1 billion, the performance of the Malaysian food industry was below economists' expectations in 2018 and 2019. Therefore, changing the traditional way of working to a world-class management system such as lean production and adopting appropriate and effective executed marketing strategies could help companies survive and stay competitive. Thus, this study attempts to develop an integrated framework of lean production practices and marketing mix strategy toward improving the business performance of Malaysian food industry companies. To have empirical evidence about these relationships, data have been collected from 187 executive managers for Malaysian food industry companies, using a self-administered questionnaire. The response rate was 31.2%, which mean 62.4% of the required sample size. The collected data have been analyzed using both descriptive statistics and multiple regressions. Correlation analysis and multiple regressions using SPSS have been performed to measure the relationship between variables and to test the hypotheses related to the study. The results of the study reveal that lean production practices and marketing mix strategy have a direct positive effect on business performance. The findings of the study also revealed that lean production practices and marketing mix strategy positively correlated. Moreover, lean production and marketing mix strategy integration affect business performance. This study contributes to the body of knowledge by investigating the relationship between lean production practices and marketing mix strategy and business performance using one comprehensive research framework. For future research, it is suggested that quantitative research, supported by exploratory research techniques such as in-depth interviews, remains important when researching this topic since the mixed approach has not yet been undertaken in this area